Bertahan dan Berkembang: Kunci Strategi dan Ukuran Keberhasilan dalam E-business - Fahmi Ardiansyah Siregar; Ira Muthia Hasibuan; Jihan Syahlina az-Zahra; Nurbaiti Nurbaiti (CV. Aksara Global Akademia, 2023)
This article delves into the importance of resilience strategies and success metrics in the context of e-business. In a rapidly changing digital era, e-businesses need to design strategies that keep them relevant and successful. This article explores a range of resilience strategies, including product and service diversification, effective online marketing, data analysis, and collaboration with third parties. These strategies are aimed at reducing risks and maximizing growth opportunities. Additionally, the article also discusses various success metrics in e-business, including revenue growth, customer retention, sales conversion, and customer satisfaction. The strong interplay between resilience strategies and success metrics is well-understood, where robust resilience strategies can support the achievement of these success metrics. Balance and adaptability in implementing resilience strategies are crucial.Success in e-business depends not only on achieving success metrics but also on a business's ability to adapt to market changes and customer needs. This article provides valuable insights for e-business stakeholders aiming for long-term success in a competitive environment.